Rethinking Europe - Delanty, Gerard (Routledge, 2005)
Dominant approaches to the transformation of Europe ignore contemporary social theory interpretations of the nature and dynamics of social change. Here, Delanty and Rumford argue that we need a theory of society in order to understand Europeanization. This book advances the case that Europeanization should be theorized in terms of: globalization major social transformations that are not exclusively spear-headed by the EU the wider context of the transformation of modernity. This fascinating book broadens the terms of the debate on Europeanization, conventionally limited to the supersession of the nation-state by a supra-national authority and the changes within member states consequent upon EU membership. Demonstrating the relevance of social theory to contemporary issues and with a focus on European transformation rather than simplistic notions of Europe-building, this truly multidisciplinary volume will appeal to readers from a range of social science disciplines, including sociology, geography, political science and European studies.